Targeting MDK Abrogates IFN-γ-Elicited Metastasis inCancers of Various Origins - Zheng, Luyu; Liu, Qun; Li, Ruijun; Chen, Shibin; Tan, Jingyu; Li, Lina; Dong, Xichen; Huang, Changzhi; Wen, Tao; Liu, Jian (Frontiers in Oncology, 2022)
IFN-γ is a pleiotropic cytokine with immunomodulatory and tumoricidal functions. It has been used as an anti-tumor agent in adjuvant therapies for various cancers. Paradoxically, recent advances have also demonstrated pro-tumorigenic effects of IFN-γ, especially in promoting cancer metastasis, with the mechanism remains unclear. This will undoubtedly hinder the application of IFN-γ in cancer treatment. Here, we verified that IFN-γ treatment led to activation of the epithelial-to-mesenchymal transition (EMT) programme and metastasis in cell lines of various cancers, including the kidney cancer cell line Caki-1, the lung cancer cell line A549, the cervical carcinoma cell line CaSki, the breast cancer cell line BT549 and the colon cancer cell line HCT116. We further disclosed that midkine (MDK), an emerging oncoprotein and EMT inducer, is a common responsive target of IFN-γ in these cell lines. Mechanistically, IFN-γ upregulated MDK via STAT1, a principle downstream effector in the IFN-γ signalling. MDK is elevated in the majority of cancer types in the TCGA database, and its overexpression drove EMT activation and cancer metastasis in all examined cell lines. Targeting MDK using a specific MDK inhibitor (iMDK) broadly reversed IFN-γ-activated EMT, and subsequently abrogated IFN-γ-triggered metastasis. Collectively, our data uncover a MDK-dependent EMT inducing mechanism underlying IFN-γ-driven metastasis across cancers which could be attenuated by pharmacological inhibition of MDK. Based on these findings, we propose that MDK may be used as a potential therapeutic target to eliminate IFN-γ-elicited pro-metastatic adverse effect, and that combined MDK utilization may expand the application of IFN-γ in cancer and improve the clinical benefits from IFN-γ-based therapies.